Impact of Valve Size on Paravalvular Leak and Valve Hemodynamics in Patients With Borderline Size Aortic Valve Annulus - Talmor-Barkan, Yeela; Kornowski, Ran; Bar, Noam; Ben-Shoshan, Jeremy; Vaknin-Assa, Hanna; Hamdan, Ashraf; Kruchin, Boris; Barbash, Israel M.; Danenberg, Haim; Perlman, Gidon Y.; Konigstein, Maayan; Finkelstein, Ariel; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter heart valve (THV) selection for transcatheter aortic valve implantation (TAVI) is crucial to achieve procedural success. Borderline aortic annulus size (BAAS), which allows a choice between two consecutive valve sizes, is a common challenge during device selection. In the present study, we evaluated TAVI outcomes in patients with BAAS according to THV size selection. Methods We performed a retrospective study including patients with severe aortic stenosis (AS) and BAAS, measured by multi-detector computed tomography (MDCT), undergoing TAVI with self-expandable (SE) or balloon-expandable (BE) THV from the Israeli multi-center TAVI registry. The aim was to evaluate outcomes of TAVI, mainly paravalvular leak (PVL) and valve hemodynamics, in patients with BAAS (based on MDCT) according to THV sizing selection in between 2 valve sizes. In addition, to investigate the benefit of shifting between different THV types (BE and SE) to avoid valve size selection in BAAS. Results Out of 2,352 patients with MDCT measurements, 598 patients with BAAS as defined for at least one THV type were included in the study. In BAAS patients treated with SE-THV, larger THV selection was associated with lower rate of PVL, compared to smaller THV (45.3 vs. 64.5%; pv = 0.0038). Regarding BE-THV, larger valve selection was associated with lower post-procedural transvalvular gradients compared to smaller THV (mean gradient: 9.9 ± 3.7 vs. 12.5 ± 7.2 mmHg; p = 0.019). Of note, rates of mortality, left bundle branch block, permanent pacemaker implantation, stroke, annular rupture, and/or coronary occlusion did not differ between groups. Conclusion BAAS is common among patients undergoing TAVI. Selection of a larger THV in these patients is associated with lower rates of PVL and optimized THV hemodynamics with no effect on procedural complications. Additionally, shift from borderline THV to non-borderline THV modified both THV hemodynamics and post-dilatation rates.